1999
DOI: 10.1161/01.cir.99.10.1379
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Administration of Vasopressin but Not Epinephrine Maintains Coronary Perfusion Pressure After Early and Late Administration During Prolonged Cardiopulmonary Resuscitation in Pigs

Abstract: Repeated administration of vasopressin but only the first epinephrine dose given early and late during basic life support CPR maintained coronary perfusion pressure above the threshold that is needed for successful defibrillation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
1
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(62 citation statements)
references
References 31 publications
4
54
1
3
Order By: Relevance
“…Th ese studies consistently demonstrated that vasopressin doses between 0.4 and 0.8 U/kg led to a signifi cantly higher coronary perfusion pressure and myocardial blood fl ow than epinephrine and were associated with a higher percentage of successfully resusci tated animals [20][21][22][23]. However, adverse cardiovascular eff ects from vasopressin have been described as well.…”
Section: Vasopressinmentioning
confidence: 97%
“…Th ese studies consistently demonstrated that vasopressin doses between 0.4 and 0.8 U/kg led to a signifi cantly higher coronary perfusion pressure and myocardial blood fl ow than epinephrine and were associated with a higher percentage of successfully resusci tated animals [20][21][22][23]. However, adverse cardiovascular eff ects from vasopressin have been described as well.…”
Section: Vasopressinmentioning
confidence: 97%
“…Η ΠΠΣΑ φαί νεται ότι είναι ο μόνος αληθινός προγνωστικός παρά γοντας για την ανάκτηση της αυτόματης κυκλοφορίας (Wenzel et al 1999). Η ΠΠΣΑ, η οποία είναι υπεύθυ νη για την αιμάτωση του μυοκαρδίου, αυξάνεται κατά τη διάρκεια των θωρακικών συμπιέσεων (Paradis et al 1990).…”
Section: συζητησηunclassified
“…CPP appears to be the only prognostic factor for ROSC (Wenzel et al 1999). CPP, the pressure respon sible for supplying the myocardium with oxygen, is significantly increased during precordial compressions (Paradis et al 1990).…”
Section: συζητησηmentioning
confidence: 99%
“…Despite its widespread use, a large body of experimental evidence from animal studies suggests that adrenaline may have no effect or even a detrimental effect on various measures of well-being and survival during resuscitation (Brown et al 1988;Wenzel et al 1999;Klouche et al 2003;Niemann and Garner 2005;Schwartz and Lagranha 2006) . High doses do not seem to improve survival and may increase adverse effects (Ditchey and Lindenfeld 1988;Lindner et al 1991b;Lindner et al 1991a;Hornchen et al 1993;Hilwig et al 2000;Voelckel et al 2000).…”
Section: Rationale For the Use Of Adrenaline In Cprmentioning
confidence: 99%